A comparison of tiotropium/olodaterol vs tiotropium alone in terms of treatment effect for chronic obstructive pulmonary disease: A meta-analysis - He, Jie (Medicine (Baltimore), 2020)
BACKGROUND: Combinations of long-acting bronchodilators with different mechanisms of action are recommended to improve prognosis and reduce risk of adverse events of chronic obstructive pulmonary disease (COPD). It is unclear whether the new combination therapy with long-acting muscarinic antagonist (LAMA) tiotropium (TIO) and long acting beta-agonists (LABA) olodaterol (OLO) was superior to tiotropium alone. METHODS: We measured the efficacy of the TIO/OLO combination vsTIO alone for COPD patients based on electronic databases up to February 2019. After rigorous quality review, data was extracted from eligible trials. All the main outcomes were pooled analysis using RevMan software. RESULTS: A total of 6 randomized controlled trials (RCTs) were identified. The pooled results of our meta-analysis demonstrated that FEV1 [MD = 0.03, 95% CI (−0.01,0.07), P = .18], FVC [MD = -0.03, 95%CI (−0.06,0.00), P = .09] and FEV1%pred [MD = 0.35, 95%CI (−0.30, 0.99), P = .29] all showed no significant difference between the 2 groups. The overall incidence of adverse effects (AEs) [OR = 1.01,95%CI (0.93,1.09), P = .87] and serious AEs [OR = 1.04,95% CI (0.82, 1.32), P = .72] in the combination group was similar to that of the TIO alone group, without statistical significance. CONCLUSION: These studies reported that the TIO/OLO combination did not show superior effects than tiotropium alone for COPD. Additionally, both therapies were well tolerated.